Improvement in the simulation tools for heat distribution predictions and control of baffle and middle divertor loads in Wendelstein 7-X. (1st February 2023) - Gao, Yu; Feng, Yuhe; Endler, Michael; Jakubowski, Marcin W.; Geiger, Joachim; Bozhenkov, Sergey; Puig Sitjes, Aleix; Pisano, Fabio; Dhard, Chandra Prakash; Naujoks, Dirk; Krychowiak, Maciej; Otte, Matthias; et al.
Abstract: In the first divertor campaign in Wendelstein 7-X (W7-X), unexpected significant heat loads were observed at particular plasma-facing components (e.g. baffle tiles and middle divertor part) which were not designed to receive high heat flux. In a prior investigation, it was concluded that the previous diffusive field line tracing (DFLT) model used for divertor design in W7-X cannot reproduce these loads, due to the missing physics in simulating the heat transport in the shaded flux tubes. To tackle this issue, two new efficient codes (DFLT_rev and EMC3-Lite) are introduced and validated against various experimental heat distributions in different magnetic configurations. The new tungsten baffle tiles have been designed with these codes and mounted in the machine, aiming for mitigated heat loads in the upcoming campaign.